Photocatalytic Hydrogen Evolution Driven by [FeFe] Hydrogenase Models Tethered to Fluorene and Silafluorene Sensitizers. Issue 2 (2nd December 2016) - Goy, Roman; Bertini, Luca; Rudolph, Tobias; Lin, Shu; Schulz, Martin; Zampella, Giuseppe; Dietzek, Benjamin; Schacher, Felix H.; De Gioia, Luca; Sakai, Ken; Weigand, Wolfgang
Abstract: It is successfully shown that photocatalytic proton reduction to dihydrogen in the presence of a sacrificial electron donor, such as trimethylamine (TEA) and ascorbate, can be driven by compact sensitizer–catalyst dyads, that is, dithiolate‐bridged [FeFe] hydrogenase models tethered to organic sensitizers, such as fluorenes and silafluorenes (1 a –4 a ). The sensitizer–catalyst dyads1 a –4 a show remarkable and promising catalytic activities as well as enhanced stabilities during photocatalysis performed under UV‐light irradiation. The photocatalysis was carried out both in non‐aqueous and aqueous media. The latter experiments were performed by solubilizing the photocatalysts within micelles formed by either sodium dodecyl sulfate (SDS) or cetyltrimethylammonium bromide (CTAB). In this study a turnover number of 539 (7 h) is achieved under optimized conditions, which corresponds to an exceptionally high turnover frequency of 77 h −1 . Theoretical investigations as well as emission decay experiments were performed to understand the observed phenomena together with the mechanisms of photocatalytic H2 generation. Abstract : Here comes the sun : Photocatalytic proton reduction to dihydrogen in the presence of a sacrificial electron donor by compact sensitizer–catalyst dyads, that is, dithiolate‐bridged [FeFe] hydrogenase models tethered to organic sensitizers such as fluorenes and silafluorenes is reported. The sensitizer–catalyst dyads show remarkable and promising catalytic activities as well as enhanced stabilities during photocatalysis performed under UV‐light irradiation.